PENGARUH MOTIVASI DAN KEMAMPUAN BERWIRAUSAHA TERHADAP KINERJA USAHA PEDAGANG KAKI LIMA DI KOTA KRAKSAAN. - Lorena, Silvia (Manajemen Bisnis, 2016)
The research purposes are to analyse the influence of motivation and entrepreneurship ability on business performance. Multiple linear regression used as a statictical tool. The result shows that motivation and enterpreneuship ability has strong influence on business performance. The recomendation from the analyses is management should maintain a good relationship with consumer and do some innovation regarding its business.